2020
DOI: 10.1096/fasebj.2020.34.s1.04430
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation can improve ovarian folliculogenesis and steroidogenesis in polycystic ovary syndrome‐induced rats

Abstract: Photobiomodulation (PBM) has been investigated and used in clinical practice, related to biomodulatory influences on cellular functions in animals and humans. The absorption of photons by the photoreceptors causes changes in the molecular configuration of these receptors and activate molecular signals in the cells. Polycystic ovary syndrome (PCOS) is one of the most common endocrine disorder in women of reproductive age, and it has a prevalence of 2% to 27%. Diagnosis of PCOS requires two of the following: pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The influence of hormonal changes on reproductive tissues revealed that leukocyte entry into uterine tissues is mostly controlled by hormones [ 96 ]. PCOS has been shown to cause histo-architectural abnormalities in the ovary [ 97 ] and uterine of rats [ 98 ].This study found that PCOS rats have the leastcorpus luteum and numerous follicular ovarian cysts, which is consistent with animal models of PCOS [ 99 , 100 ]. Reduced levels of testosterone, FSH, LH, and antioxidant activity might be linked to decreased ovarian weight, uterine length and weight, endometrium thickness, and endometrial gland numbers.…”
Section: Discussionsupporting
confidence: 87%
“…The influence of hormonal changes on reproductive tissues revealed that leukocyte entry into uterine tissues is mostly controlled by hormones [ 96 ]. PCOS has been shown to cause histo-architectural abnormalities in the ovary [ 97 ] and uterine of rats [ 98 ].This study found that PCOS rats have the leastcorpus luteum and numerous follicular ovarian cysts, which is consistent with animal models of PCOS [ 99 , 100 ]. Reduced levels of testosterone, FSH, LH, and antioxidant activity might be linked to decreased ovarian weight, uterine length and weight, endometrium thickness, and endometrial gland numbers.…”
Section: Discussionsupporting
confidence: 87%
“…The PCOS induction lowered significantly all investigated parameters except D2, while the strain differences between WK and SHR were observed only regarding OV/ BW index. Besides the well-known parameter termed 'gonadosomatic index' (Alves et al 2019), we tried to estimate a new parameter -OV/BW index, which gave a better insight into group differences. Therefore, we assumed that OV/BW index might be a useful tool for estimating OV alterations in PCOS rat studies.…”
Section: Discussionmentioning
confidence: 99%